THE USE OF NON-STANDARD INDONESIAN LANGUAGE: STUDENTS' ERRORS IN WRITING ACADEMIC PAPAERS - Bustomi Bustomi; Zelvia Liska Afriani (Diglosia : Jurnal Pendidikan, Kebahasaan, dan Kesusastraan Indonesia, 2020)
Abstract: Previous research has shown that writing is one of the most difficult language skills among the four other language skills. It stems from the fact that writing is an activity of expressing ideas of the mind that requires a variety of linguistic and non-linguistic competencies. This linguistic competence includes knowledge of morphology, syntax, and discourse. In writing, a person is required to use the correct choice of standard words, compose effective sentences, and arrange coherent paragraphs. The non-linguistic competence is the knowledge of information and scientific material owned by the author. This descriptive qualitative research aims to identify the errors of IAIN Bengkulu students in writing academic papers in Indonesian. Data was collected from PGMI and PAI student theses which were then analyzed through four stages, namely preparation, data collection, data analysis, and processing/presenting the results of data analysis. The results showed that the errors that were often found in the writing of students (including lecturers) both in the form of papers and thesis included the use of standard words, affixations, and effective sentences. Practically, this research is expected to be able to provide benefits for students and other academics in writing and producing higher quality scientific work.